Health Information Technology Workforce Needs of Rural Primary Care Practices. Issue 1 (25th July 2014) - Skillman, Susan M.; Andrilla, C. Holly A.; Patterson, Davis G.; Fenton, Susan H.; Ostergard, Stefanie J.
Abstract Purpose This study assessed electronic health record (EHR) and health information technology (HIT) workforce resources needed by rural primary care practices, and their workforce‐related barriers to implementing and using EHRs and HIT. Methods Rural primary care practices (1, 772) in 13 states (34.2% response) were surveyed in 2012 using mailed and Web‐based questionnaires. Findings EHRs or HIT were used by 70% of respondents. Among practices using or intending to use the technology, most did not plan to hire new employees to obtain EHR/HIT skills and even fewer planned to hire consultants or vendors to fill gaps. Many practices had staff with some basic/entry, intermediate and/or advanced‐level skills, but nearly two‐thirds (61.4%) needed more staff training. Affordable access to vendors/consultants who understand their needs and availability of community college and baccalaureate‐level training were the workforce‐related barriers cited by the highest percentages of respondents. Accessing the Web/Internet challenged nearly a quarter of practices in isolated rural areas, and nearly a fifth in small rural areas. Finding relevant vendors/consultants and qualified staff were greater barriers in small and isolated rural areas than in large rural areas. Discussion/Conclusions Rural primary care practices mainly will rely on existing staff for continued implementation and use of EHR/HIT systems. Infrastructure and workforce‐related barriers remain and must be overcome before practices can fully manage patient populations and exchange patient information among care system partners. Efforts to monitor adoption of these skills and ongoing support for continuing education will likely benefit rural populations.